Od "wyzwolenia od faszyzmu" do "bolszewickiej okupacji". Kultura pamięci zakończenia drugiej wojny światowej w prasie lubuskiej = From the "liberation from fascism" to the "Soviet occupation". Memory Culture of the end of the Second World War in the Lubusz press - Wasilewski, Krzysztof (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article is a critical analysis of the press discourse dedicated to the anniversary of the end of World War II. The basic research material was used by magazines published in the Lubusz Region between 1985 and 1995. Such a timeframe was dictated by the desire to compare the ways of commemorating the anniversary in the last decade of People's Poland and the first decade of the Third Republic. By analyzing the emerging motives and key concepts, the author tries to answer the question of how the discourse was changing under the influence of various types of political, social and cultural events. The article is also an attempt to define the basic determinants of collective memory of the local community and the role played by the media in shaping it.
Keywords: II wojna światowa (1939-1945); analiza dyskursu; prasa; prasa lokalna; czasopisma; czasopisma lokalne; Ziemia Lubuska; rocznice; pamięć zbiorowa; world war II; discourse analysis; press; local press; magazines; local magazines; Lubusz Land; anniversaries; collective memory